Deep Learning Application for Plant Classification on Unbalanced Training Set - Pereira, Rafael S.; Porto, Fabio (Anais do Brazilian e-Science Workshop (BreSci); 2019: Anais do XIII Brazilian e-Science WorkshopDO - 10.5753/bresci.2019.10023, 2019)
Deep learning models expect a reasonable amount of training instances to improve prediction quality. Moreover, in classification problems, the occurrence of an unbalanced distribution may lead to a biased model. In this paper, we investigate the problem of species classification from plant images, where some species have very few image samples. We explore reduced versions of imagenet Neural Network winners architecture to filter the space of candidate matches, under a target accuracy level. We show through experimental results using real unbalanced plant image datasets that our approach can lead to classifications within the 5 best positions with high probability.